Critical Analysis Of The Graduate Competency Standards Policy And Basic Education Curriculum Content Standards - Rohmah, Afwatun (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The implementation of the 2013 curriculum needs to be analyzed what policies are used in the curriculum structure because its implementation is still not so perfect, policies will be analyzed that enable students to achieve the goals of success in learning which is motivated by the Graduate Competency Standards (SKL) policies and standards content which is the beginning of the formation of the learning process. Graduate Competency Standards (SKL) are used as a reference or minimum standard to determine the success of student learning outcomes. Whereas content standards are used to determine what components must be achieved in the learning process, these content standards contain Core Competencies (KI) and Basic Competencies (KD). Both of these components are used and are very important in the learning process. The research method used is library research or literature study where data will be collected from several articles, journals, or books that have been fixed or have been published and an analysis of their contents will be carried out. The purpose of this study was to determine SKL policies and content standards in the 2013 curriculum. The results obtained in this study were SKL and content standards covering 3 aspects namely cognitive, affective, and psychomotor. SKL for the assessment criteria is carried out in each subject and at each different level of education. Content standards are prepared to become the basis for determining SKL.